Utilization of Green Mussel Shell Waste in Efforts to Improve the Economy of Coastal Communities in Karangantu: Pemanfaatan Limbah Cangkang Kerang Hijau Dalam Upaya Peningkatan Ekonomi Masyarakat Pesisir Pantai Karangantu - Anis Masyruroh; Iroh Rahmawati; Nia Kurniatillah; Siti Hotimah; Susilawati, Susilawati (Universitas Lancang Kuning, 2024)
Utilization of green mussel shell waste (Perna viridis) is one of the potential efforts to improve the economy of coastal communities, especially in Karangantu Beach. Green mussel shells that have so far only been thrown away or used as waste can be processed into various products with added value, such as organic fertilizer, raw materials for handicrafts, and animal feed. This Community Service Program aims to process green mussel shells into flour as an addition to animal feed, financial management training for the green mussel cultivation group of the Karya Sinar Bahari cooperative, and socialization of clean and healthy living behavior, as well as socialization of the blue economy concept and the potential of Tanggul Jaya Village as a blue economy driver. The methods used are institutional approaches, participatory approaches, discussion and training methods, data obtained from surveys and interviews with local fishermen and craftsmen. The results show that this waste processing not only reduces environmental pollution, but also creates new jobs and improves community welfare. The existence of financial management training for mussel cultivation groups can manage resources well, and financial planning and cost control are more measurable. With effective socialization of PHBS and blue economy, these two concepts can support each other to create a healthier and more sustainable society. It is hoped that the use of green mussel shells can be a sustainable solution for the coastal communities of Karangantu Beach in facing economic challenges.